Pengaruh Promosi Penjualan dan Kualitas Pelayanan terhadap Loyalitas Konsumen pada Chinoss Coffeespace di Pekanbaru - Ricky Aryanandes; Evawani Elysa Lubis (Lembaga Pengembangan Kinerja Dosen, 2024)
Since the development of lifestyles has become increasingly rapid, the activity of drinking coffee has become a lifestyle in itself. We can see one of these phenomena from the rise of coffee shops that are scattered around offering one stop shopping. Chinoss Coffeespace is a Coffee Shop in Pekanbaru. Coffee Shop initially only provided a place to drink coffee and tea quickly. This research is in line with the Stimulus Organism Response (S-O-R) theory where in essence, good and appropriate sales promotions and service quality can also cause good reactions from consumers, namely loyalty from consumers themselves, and vice versa, if sales promotions and The quality of the service provided is poor so it gets less reaction from consumers, namely consumers do not become loyal to Coffeeshop. This research aims to find out how much sales promotions at Chinoss Coffeespace can influence consumer loyalty.This research uses quantitative research methods, survey methods. The population in this study are consumers who have a loyalty card from Chinos Coffeeshop. In this sample, researchers took a sample of 154 consumers. And also to find out how much the quality of service at Chinoss Coffeespace can influence consumer loyalty. From the results obtained from the Chinoss owner, 1000 cards have been distributed to customers, where each customer must collect 4 cards to be able to exchange them and get a tumbler prize.That the coefficient of determination is 0.812 or equal to 81.2%, this means that variable X1 and Variable X2, in this case Sales Promotion and Customer Quality in the case of Chinoss Coffeespace, can influence variable Y, namely Consumer Loyalty. After the data was processed using the SPSS version 25 application, the researcher knew that the calculated F value of 325.660 had a significance level of 0.000. Therefore, because the significance value in this research is 0.000 which is smaller than the standard significance of 0.05, we can conclude that variables X1 (sales promotion) and X2 (service quality) have an influence on variable Y (Consumer Loyalty). It can be concluded that sales promotion as variable X1 and service quality as variable X2 influence consumer loyalty as variable Y for Chinoss Coffeespace consumers.